Implementasi Metode A BA TA TSA Dalam Pembelajaran Al Quran (Studi Kasus di Rumah Tahfizh Daarus Sunnah Sekayu Kabupaten Musi Banyiasin) - Supratama, Riky; Sopian Saputra, Muhammad; Nashihin, Husna (Lembaga Penelitian Dan Pengabdian Masyarakat Stai Brebes, 2023)
Home Tahfizh Daarus Sunnah Sekayu Musi Banyuasin district, is an educational institution under the umbrella of At-Turost Al-Islamy Foundation and is a branch of the 23rd Islamic Center Bin Baz, the Tahfizh Daarus Sunnah Sekayu House is more focused on teaching the reading of the Qur’an with the A Ba Ta Tsa method written by Ustad Bambang Abdullah who is domiciled in Jakarta. Throthis time the teaching of reading the Qur'an did not use special methods so the ability of students is still not effective. Then do not forget to read the Qur'an in the right way. This research aims to identify and analyze related to the implementation of the learning of the Qur’an with the method A BA TA TSA at the House of Tahfizh Daarus Sunnah Sekayu. This research is a fieldresearch, which is more focused on elementary school students studying at the Tahfizh Daarus Sunnah Sekayu House. Data collection techniques are done through documentation, observation and interviews. The method used in this research is the Qualitative method. The results of this study revealed three findings: Implementation, implementation and evaluation of the reading of the Qur'an using the A Ba Ta Tsa method at the House of Tahfizh Daarus Sunnah Sekayu district of Musi Banyuasin.